2019
DOI: 10.1159/000499173
|View full text |Cite
|
Sign up to set email alerts
|

Two-Generation Transmission of Trisomy 18p: Prenatal Diagnosis in a Woman with Mild Intellectual Disability

Abstract: Trisomy 18p is a rarely observed chromosomal aberration. Only 31 cases have previously been described in the literature. Trisomy 18p is associated with mild to moderate phenotypic anomalies and intellectual disability. Here, we report on a pregnant woman in whom noninvasive prenatal testing indicated a high risk of fetal trisomy 18. Prenatal diagnosis and karyotyping of the parents were performed and demonstrated that both the mother and the fetus had a derivative chromosome 15 with a segment of unknown origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Since the first report of partial monosomy 9p in 1973, 9 over 100 cases have been documented 10 . Unlike full or mosaic trisomy 18 or partial trisomy 18q, trisomy 18p has been rarely reported with only about 32 cases of trisomy 18p having been published to date 11 . Reported cases involving a translocation between chromosomes 9 and 18 resulting in partial monosomy 9p and partial trisomy 18p are even rarer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of partial monosomy 9p in 1973, 9 over 100 cases have been documented 10 . Unlike full or mosaic trisomy 18 or partial trisomy 18q, trisomy 18p has been rarely reported with only about 32 cases of trisomy 18p having been published to date 11 . Reported cases involving a translocation between chromosomes 9 and 18 resulting in partial monosomy 9p and partial trisomy 18p are even rarer.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Unlike full or mosaic trisomy 18 or partial trisomy 18q, trisomy 18p has been rarely reported with only about 32 cases of trisomy 18p having been published to date. 11 Reported cases involving a translocation between chromosomes 9 and 18 resulting in partial monosomy 9p and partial trisomy 18p are even rarer. Our review of published reports found only one such report.…”
Section: Introductionmentioning
confidence: 99%